Pelatihan Teknik Cuci Tangan (WHO, 2009) Pada Guru Dan Siswa SDIT Anak Soleh Mataram - E. Hagni Wardoyo; Didit Yudhanto; Hamsu Kadriyan; Triana Dyah Cahyawati; Yoga Pamungkas Susani; Titi Pambudi Karuniawaty (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2018)
Prevention of infectious diseases in hospital, for example applied correct hand hygiene technique has been required applied its in the community. Due to a rise incidence of infectious diseases in the community, the capacity to perform hand hygiene technique has become important. Elementary student and their teacher are an effective agent of change in the community can help to socialize this important matter according to WHO (2009) hand hygiene technique. Community Devotion and Empowerment Team, Faculty of Medicine Mataram University had been undergone Hand hygiene technique to 110 students and 6 teachers of SDIT Anak Soleh Mataram. Learning strategies to elementary school age takes interesting technique using videos and demonstration using Lumigerm® lotion, a washable germ mimic that invisible under daylight and can only be seen under UV light. The results showed an increase in understanding technique from 34.5 to 82.6 (pretest and post test, respectively) and 88% participants were able to diminish lumigerm lotion properly after hand hygiene demonstration under UV light checked.